Hydrodynamics of Bubbling Fluidized Bed - Agrawal, Vaibhav (Curtin University, 2018)
Computational fluid dynamic (CFD) simulations and electrical capacitance volume tomography (ECVT) experiments were conducted to study the gas-solid hydrodynamics in bubbling fluidized beds having mono- and bi-dispersed solids. The major contributions of this thesis are investigations of (i) gas-solid drag models to improve CFD-DEM (discrete element model) predictions, (ii) initial bed condition on mixing of bi-dispersed solids, and (iii) ECVT measurements of bubble properties.